Analisis Dampak Pembangunan Lapangan Badminton Di Desa Winong Kecamatan Ngampel Kabupaten Kendal: Partisipasi Masyarakat Dan Mahasiswa KKN Dalam Meningkatkan Kesejahteraan Sosial - Ummi Kultsum Sakinah; Nurrohman Fajar Aziz; Safitri Fauziah Rahayu (Jurnal Pelayanan Masyarakat, 2024)
This study aims to analyze the impact of the construction of a badminton court, which resulted from a collaboration between students from the 18th Independent Initiative Program (MIT) Real Work Lecture (KKN) at Posko 74 of Walisongo Univercity. The collaboration between students and local residents in Winong Village (Ngampel District, Kendal Regency), particularly those residing in RT 1 RW 2 Salaman Hamlet, has been pivotal in enhancing the well-being of the community. This study employed a qualitative approach with descriptive methods, and data were gathered through in-depth interviews, participatory observation, and documentation of the development process. The findings of this study demonstrate that the construction of the badminton court in Winong Village was not only successful in providing the community with much-needed sports facilities, but it also resulted in the strengthening of social solidarity and the spirit of mutual cooperation between residents and KKN students. This article underscores the significance of community involvement and the part played by local leaders in village development initiatives, where the spirit of mutual assistance serves as a robust social capital. The assessment and enhancement of public facilities are also essential to guarantee sustainability and reinforce social networks within the community.